2013
DOI: 10.1242/jeb.080523
|View full text |Cite
|
Sign up to set email alerts
|

An androgenic gland membrane-anchored gene associated with the crustacean insulin-like androgenic gland hormone

Abstract: SUMMARYCrustacean male sexual differentiation is governed by the androgenic gland (AG) and specifically by the secreted insulin-like AG hormone (IAG), thus far identified in several decapod species including the Australian red claw crayfish Cherax quadricarinatus (termed Cq-IAG). While a few insulin-like AG genes have been identified in crustaceans, other AG-specific genes have not been documented until now. In the present study, we describe the recent identification of a non-IAG AG-specific transcript obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…A technique studied for both aquaculture and invasive crayfish species is the "masculinization of individuals". The insulin-like androgenic gland hormone (IAG) plays a decisive role in sexual differentiation, with the possibility of manipulating crayfish populations in order to produce sexually altered populations, such as monosex populations, which will not reproduce further [127,128]. The potential of intervention through sex-change induction on established populations of NICS illuminates new management possibilities.…”
Section: Monosex Populationsmentioning
confidence: 99%
“…A technique studied for both aquaculture and invasive crayfish species is the "masculinization of individuals". The insulin-like androgenic gland hormone (IAG) plays a decisive role in sexual differentiation, with the possibility of manipulating crayfish populations in order to produce sexually altered populations, such as monosex populations, which will not reproduce further [127,128]. The potential of intervention through sex-change induction on established populations of NICS illuminates new management possibilities.…”
Section: Monosex Populationsmentioning
confidence: 99%
“…Amongst the annotated upregulated transcripts was an orthologue of a recently identified AG-specific transcript, characterized in C. quadricarinatus : the AG-specific membrane-anchored protein ( Cq-MAG ) [Rosen et al, 2013a]. However, in S. verreauxi , it appears that Sv-MAG is not AG-specific as it also shows expression in both testis and ovary [but not in male or female brain, eyestalk, antennal gland, hepatopancreas, or male muscle, as demonstrated through both RPKM (all <1) and RT-PCR analyses ( fig.…”
Section: Functional Characterization Of the Mature Androgenic Gland Dmentioning
confidence: 99%
“…The work of Jin et al [2013] identified a total of 47 sex-related gene families in the AG of M. nipponense , clear evidence of the AG's function in sexual development. However, with the exception of the membrane-anchored AG-specific factor (Cq-MAG) characterized in Cherax quadricariantus [Rosen et al, 2013a], to our knowledge, besides IAG no other AG-specific factors have been characterized to date.…”
mentioning
confidence: 95%
“…In addition to IAG , MAG is also broadly expressed. Given that MAG was found to directly interact with IAG [ 39 ], this broad expression further supports a more diverse role for IAG in reproduction and metabolism. Interestingly, MAG expression overlaps with that of ILP1 .…”
Section: Resultsmentioning
confidence: 87%
“…Upon secretion, IAG is chaperoned in the hemolymph by an insulin-like growth factor-binding peptide (IGFBP) which is abundantly expressed across tissues [ 13 , 38 ]. IAG secretion is further facilitated by a membrane-anchored AG-specific factor (MAG), identified initially in the redclaw crayfish Cherax quadricarinatus [ 39 ] and later in the eastern spiny lobster Sagmariasus verreauxi , where a slight expression in the gonads was also detectable [ 11 ]. Modeling analysis concluded that the neural-derived ILPs share the same binding characteristic to IGFBP as IAG [ 8 ], suggesting they might also compete with IAG for receptor binding.…”
Section: Introductionmentioning
confidence: 99%